THE FUNCTIONING OF BIBLICAL METAPHOR OF EXILE/EXODUS IN A MEMOIR DISCOURSE (ON THE MATERIAL OF MEMOIR TEXTS RUSSIAN EMIGRATION “FIRST WAVE”) (Филологический класс, 2019)
The biblical metaphor of exile/exodus as a component of the tropics in the memoir discourse of the Russian emigration of the “first wave” did not become the subject of a special study. Meanwhile, an analysis of the literary memoirs of the Russian Diaspora shows that often the metaphor, including the biblical metaphor of exile/exodus, becomes a way of implementing author’s intentions. Thus, the purpose of this study is to analyze the metaphorical embodiment of intentions as one of the directions of their study on the material of the biblical metaphor of exile / exodus. In the work, a general philological method of interpreting memoirs was used, which implies the literary and linguistic methods of authorial intentions. The article outlines the theoretical basis for studying the tropics of memoir discourse, actualizes the issue of studying this phenomenon on the material of the Russian emigration of the “first wave”; considered the relationship of the intention and its metaphorical embodiment in the memoir text, proposed a method of investigation of intentions using metaphor, describes the intentional groups of biblical metaphors of exile / exodus in the texts of memoirs as a set of intentions combined to reflect on a wide range of events that influenced historical processes and marked them role in the texts of memoirs. The object of the research is the texts of memoirs of the Russian emigration of the “first wave”. The chosen perspective of the study allowed deepening the understanding of the nature of the communicative act in the memoirs, which was facilitated by the allocation of linguistic means of expression of the intended purpose. Considering that the intention is usually not verbally expressed in the text, the allocation of these means of expression as cognitive-stylistic techniques allowed the author to reveal literary meanings generated by the historically established, socially defined complex of culture – in this case, the era of the Silver Age, as well as the culture of Russian Abroad. The use of this methodology contributes to the further study of the picture of the world of the emigrant and contributes to the deepening of the understanding of the creative consciousness of the artist who lived in the era of historical change.